а)4х+у=6 4х+у=6 б)-х+у=12 -х+у=12 в)2х-5у=15 2х-5у=15
у=6/4х 4х=6-у у=12+х -х=12-у /(-1) -5у=15-2х /(-5) 2х=15+5у /2
у=1,5х х=(6-у):4 х=y-12 у=0,4х-3 х=7,5+2,5у
х=1,5-у/4
г)3х/2-у=6 3х/2-у=6
-у=6-3х/2 /(-1) 3х/2=6+у
у=1,5х-6 3х=6+у /*2
3х=12+2у /3
х=4+2/3у
а)4х+у=6 4х+у=6 б)-х+у=12 -х+у=12 в)2х-5у=15 2х-5у=15
у=6/4х 4х=6-у у=12+х -х=12-у /(-1) -5у=15-2х /(-5) 2х=15+5у /2
у=1,5х х=(6-у):4 х=y-12 у=0,4х-3 х=7,5+2,5у
х=1,5-у/4
г)3х/2-у=6 3х/2-у=6
-у=6-3х/2 /(-1) 3х/2=6+у
у=1,5х-6 3х=6+у /*2
3х=12+2у /3
х=4+2/3у
14_1/6-(8_9/10-5_2/3)= 85/6-89/10+17/3=(85*6-89*3+17*10)/30=(425-267+170)/30=328/30=10_28/30=10_14/15